Phytochemical and microbiological evaluation of a local medicinal plant bacopa monnieri (l.) Penn - Awang, Mohamed; Rahman, Md. Mokhlesur (In-IJCPR, 2012)
This research work was carried out to investigate the phytochemical constituents as well as the pharmacological prooperties of ‘Bacopa monnieri’. The project work reveals that the plant has antibacterial and antimutagenic activities. Thus an attempt was made to reinvestigate aforementioned antimicrobial as well as cytotoxic properties for the bark constituents. The following aspects of Bacopa monnieri (L.) Penn., (root bark and stem bark) have been intended to be accomplished in this research project: Review of the chemical constituents and biological activities of Bacopa monnieri (L.) Penn and the successive isolation of the dried bark (root and stem) with alcohol. The powdered plant was successively extracted with ether solvent. The Phytochemical screening of the extracts showed the presence of glycosides, alkaloids and flavonoids. The antimicrobial investigation showed that ether extract showed antimicrobial activity against four bacteria and one fungus. From the literature review to was also found that the plant has direct therapeutic effects on piles, dysentery, dyspepsia, diarrhea, vomiting, giddiness, worms, burning of the skin and menorrhoea.